Aplikasi Sistem Informasi Data Statistik Berbasis Web Di Badan Pusat Statistik Kabupaten Cirebon - Novianti, Dian (INTI TALAFA: Jurnal Teknik Informatika, 2014)
Statistics have a role to change the information in the form of data into an information . Statistics,originally used to perform data collection and analysis of population data. The population data analysis aims to determine the number, distribution, composition, and population growth from year to year. Statistics is now becoming a necessity for informing us about the development of a field, but not a few of us who struggle to obtain such data. Statistical data presentation system that long just to reach the agencies and local governments only. In line with the development of information technology, Statistics Cirebon should have a web-based information system that is accessible to all people so as to provide convenience for the user in terms of search statistics. The application is built with a web-based computer technology, programming language PHP and uses MySQL as its database. Data collection techniques used in this study using observation, interviews and literature studies. While the method of using the waterfall model of development. This application allows the public to search for statistical data, such as demographic data, geographic, socia, economic, governmental, and other data related to statistical activities, especially data that is in the district of Cirebon. Keywords: Statistics, Data, Information Systems, Web.